Transformation of state policy for regulating labor and education markets in the digital reality of modern society - O. K. Mineva; V. S. Minev; V. E. Letichevskaya (Новые технологии, 2020)
Global penetration of digital tools into everyday life dictates a significant change in approaches to defining requirements for specialists of the present and future. High speed of technological changes and total algorithmization of typical tasks significantly reduce the list of traditional professions and create conditions for the emergence of technological unemployment. A significant problem for all subjects of the labor market is the natural transformation of models of their interaction with each other. Reducing the time lag of a technological wave duration plays an important role here. This affects directly the development trends of the real economy, education, and labor markets. In addition, the paradigm of state management of labor and education markets is expected to undergo radical changes. High transparency of the borders of national labor markets and development of on-line education dictate the need to synchronize approaches to models of public administration in these areas. In the framework of this article we have identified the prerequisites for transforming the existing paradigm of interaction between labor market actors and have proposed measures for immediate synchronous work of governments of different states in order to offset possible negative consequences of digitalization of the economy.